POTENTIAL OF EXOSOMES ISOLATED FROM WHARTONâS JELLY MESENCHYMAL STEM CELLS PRECONDITIONED WITH COBALT (II) CHLORIDE (COCL2) AND L-ASCORBIC ACID (LAA) FOR CHONDROGENIC DIFFERENTIATION - Prawitasari, Salindri
Cell-free therapy is an alternative treatment that can be used in cartilage repair to overcome the shortcomings of the microfracture method, osteochondral transplantation, and chondrocyte implantation, including pain, limited tissue availability, and the formation of fibrocartilage. Exosomes are vesicles formed from endosomal fusion of multivesicular bodies with plasma membranes, with size range of 30-150 nm produced by various cell types, including mesenchymal stem cells (MSCs). Exosomes play a role in cell communication and signaling, as well as mediate various biological functions such as cell growth, migration, and proliferation. Exosomes from MSCs are known to induce chondrocyte proliferation and chondrogenic differentiation in stem cells through secretion of growth factors and miRNAs as well as carriers of certain miRNAs. The cargo contained in exosomes depends on the conditions of the cells that secrete them. Research has shown that administration of cobalt (II) chloride (CoCl2) and L-ascorbic acid (LAA) can induce chondrogenic differentiation of MSCs, but there has been no study on exosomes of hWJ-MSCs treated with CoCl2 and LAA and their potential in inducing chondrogenesis. Therefore, this study aimed to isolate and characterize exosomes from Human Wharton's Jelly Mesenchymal Stem Cells (hWJ-MSCs) treated with CoCl2 and LAA, as well as to determine the potential of exosomes in inducing chondrogenic differentiation. This study used hWJ-MSCs isolated from the umbilical cord, then the isolated hWJ-MSCs was characterized morphologically; multipotency ability was performed by inducing hWJ-MSCs with osteogenic, chondrogenic, and adipogenic differentiation medium; and analysis of specific surface markers. Cultures of hWJ-MSCs passage 6 were treated with CoCl2 at various concentrations (25, 50, 100, 200, and 400 ?M) for 24 and 48 hours and then analyzed for cytotoxicity by MTT assay. The LAA concentration was determined based on previous research, which was 250 ?M. Cultures of hWJ-MSCs passage 5 which were treated with the addition of CoCl2, LAA, combination of CoCl2+LAA, and controls, then the exosomes were isolated. The isolated exosomes were morphologically characterized using Transmission Electron Microscopy (TEM) and analyzed for specific CD63 markers by ELISA. Particle size and concentration of exosomes were analyzed by Nanoparticle Tracking Analysis (NTA). Internalization of exosomes in hWJ-MSCs was carried out by labeling exosomes with PKH67. The potential of exosomes in inducing chondrogenic differentiation was carried out by giving exosomes from untreated hWJ-MSCs and treated with the combination of CoCl2+LAA to hWJ-MSCs for 21 days. The analysis of chondrogenesis markers such as glycosaminoglycan accumulation (GAG) was analyzed using the Alcian Blue assay and the presence of type II collagen was analyzed using immunocytochemistry. Based on the results of the study, it was found that hWJ-MSCs was fibroblast-like in shape and had positive results for MSCs markers, namely CD73 (97.9%), CD90 (92.3%), and CD105 (91.2%); and negative for the CD34, CD45, CD11b, and CD19 markers. Based on the results of the MTT assay, hWJ-MSCs were treated with CoCl2 with a concentration of 25 ?M, LAA 250 ?M, and combination of 25 ?M CoCl2 + 250 ?M LAA for 48 hours and the exosomes were isolated. The results of visualization with TEM showed that the exosomes were spherical. Based on the results of NTA, exosomes from untreated hWJ-MSCs, treated with LAA, and combination of CoCl2+LAA had a concentration of 2.133 x 107; 1.169 x 108; 3.244 x 107 particles/mL. The concentration of exosomes from CoCl2 treatment was not detected. The average exosome size of the untreated hWJ-MSCs, treated with CoCl2, LAA, and combination of CoCl2+LAA, respectively, was 114 nm with a modal size of 125 nm, 100 nm with a modal size of 24.98 nm, 101 nm with a modal size of 96.38 nm; and 110 nm with a modal size of 149 nm. The results of CD63 analysis showed that the concentration of CD63 in exosomes from untreated hWJ-MSCs, treated with CoCl2, LAA, and combination of CoCl2+LAA was 110.50±6.19 pg/mL; 30.50±4.42 pg/mL; 4.25±0.88 pg/mL; and 43.63±1.77 pg/mL. The internalization of exosomes from hWJ-MSCs treated with the combination of CoCl2+LAA was clearly visible at 6 h of incubation. Administration of exosomes from untreated hWJ-MSCs and treated with the combination of CoCl2+LAA to hWJ-MSCs for 21 days showed an increasing accumulation of GAG. The results of immunocytochemical observations showed that type II collagen began to be synthesized after the 7th day of treatment and its synthesis increased on the 21st day. Based on the results of the study, it can be concluded that the treatment of CoCl2, LAA, and combination of CoCl2+LAA in hWJ-MSCs affected the size and concentration of secreted exosomes. Exosomes from untreated and CoCl2+LAA combination-treated hWJ-MSCs could induce chondrogenic differentiation.